IMPLEMENTASI NILAI-NILAI AJARAN ISLAM WASATHIYAH DALAM MENGHADAPI PANDEMI COVID-19 - Sri Lestari (PASCASARJANA UNISNU, 2020)
AbstractThis research describes the implementation the values of Islam wasathiyah teaching in facing of the COVID-19 pandemic. In accordance with the policy of the Prophet Muhammad peace and blessing for him said “If you hear about plague in a country, then don’t enter it. But if there is an outbreak somewhere you are be, then don’t you leave that place.” (Hadiths from Bukhari and Muslim). So referring to current conditions, with the presence of the corona virus taht is currently sweeping around the world including Indonesia, it is very relevant if the Prophet Muhammad’s policy is applied in the context of facing the current situation and consition, namely by implementimg social distancing or even locking down red zones places. We must endeavor and be patient and increase prayer and worship to draw closer to Allah during COVID-19 pandemic. In dealing with epidemic, we must remind and help each other in various matters including in terms of worship and economy. One of the way is forming WhatsApp group for Qotmil Qur’an.Keywords: COVID-19; Islam Wasathiyah; Islamic Values